Implementasi Manajemen Pendidikan Dalam Meningkatkan Kualitas Belajar Siswa - Muchamad Syaifudin (PUSAT PUBLIKASI ILMIAH SEKOLAH TINGGI AGAMA ISLAM (STAI) AL-YASINI PASURUAN, 2025)
This study highlights the importance of educational management in improving the quality of student learning at Al Asmuny Islamic Junior High School, Kraton, Pasuruan. Education is not simply a process of transferring knowledge, but also the formation of character and moral values, which require effective management to optimally achieve learning objectives. Based on observations, obstacles remain in the implementation of management functions, particularly in the planning and evaluation aspects of learning. This study used a descriptive qualitative approach using observation, interviews, and documentation techniques. Data analysis refers to the interactive model of Miles and Huberman (1994) and its validity was tested through triangulation. The results indicate that the four management functions—planning, organizing, implementing, and supervising—operate quite effectively and have a positive impact on improving learning outcomes. Data indicate an average increase in grades of 10.4% after optimal management implementation. This success is influenced by participatory leadership, teacher competence, and parental support. However, teachers' limited time and the lack of technology utilization remain challenges. Overall, this study confirms that collaborative, focused, and sustainable educational management is the key to improving learning quality and developing students' Islamic character.